Microbial Communities and Diversities in Mudflat Sediments Analyzed Using a Modified Metatranscriptomic Method - Yan, Yong-Wei; Jiang, Qiu-Yue; Wang, Jian-Gong; Zhu, Ting; Zou, Bin; Qiu, Qiong-Fen; Quan, Zhe-Xue (Frontiers in Microbiology, 2018)
Intertidal mudflats are land–sea interaction areas and play important roles in global nutrient cycles. However, a comprehensive understanding of microbial communities in these mudflats remains elusive. In this study, mudflat sediment samples from the Dongtan wetland of Chongming Island, the largest alluvial island in the world, were collected. Using a modified metatranscriptomic method, the depth-wise distributions of potentially active microbial communities were investigated based on small subunit ribosomal RNA (SSU rRNA) sequences. Multiple environmental factors were also measured and analyzed in conjunction with the prokaryotic composition profiles. A prokaryotic diversity analysis based on the metatranscriptome datasets revealed 2- or 3-fold higher diversity indices (associated with potentially active microbes participating in biogeochemical processes in Dongtan) compared with the diversity indices based on 16S rRNA gene amplicons. Bacteria were numerically dominant relative to archaea, and the potentially active prokaryotic taxa were mostly assigned to the bacterial phyla Chloroflexi, Acidobacteria, and Bacteroidetes and the classes Delta- and Gamma-proteobacteria, along with the archaeal lineages Miscellaneous Crenarchaeotic Group and the order Thermoplasmatales. The total nitrogen and carbon content of the sediment samples were environmental factors that significantly affected the depth-wise distributions of both bacterial and archaeal communities. Furthermore, the activity of potentially active taxa (including the prevalent order Desulfobacterales and family Anaerolineaceae) appeared to be significantly underestimated by PCR-based methods, notably at the DNA level, and indicates that using normal PCR amplification of DNA limits the study of potential microbial activity. This is the first study of potentially active microbial communities in depth-wise sediments from Dongtan. The improved knowledge of microbial communities in Dongtan provides a foundation for exploring biogeochemical cycling and microbial functions.